Pengaruh Layanan Toko Ritel, Keragaman Produk, Dan Promosi Terhadap Keputusan Pembelian Tidak Terencana (Studi Kasus Pada Konsumen Toko Sardo Malang) - Mohammad Rasuli; Rois Arifin; Fahrurrozi Rahman (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract The purpose of this study is to analyze the simultaneous impact of retail store services, product diversity, and promotions on unplanned purchasing decisions, analyze the partial impact of retail store services, product diversity, and promotions on unplanned purchasing decisions and to analyze among retail store services, product diversity. , and the promotion of variables that have a dominant influence on unplanned purchasing decisions. The population is buyers at Sardo Swalayan with a total sample of 90 respondents. Based on the results of research and discussions that have been carried out, the following conclusions can be drawn: At the Sardo Malang store, retail services, product diversity, and promotions simultaneously affect unplanned purchasing decisions. Analysis of the partial impact of retail store services, product diversity, and promotions on unplanned purchasing decisions at Sardo Malang stores. Based on the results of the regression coefficient (b) for each variable, it can be seen that product diversity has a dominant influence on unplanned purchasing decisions at the Sardo. Keywords: Retail Store Service, Product Diversity, Promotion And Purchase Decision